Chemical synthesis of 3D copper sulfide with different morphologies for high performance supercapacitors application. Issue 18 (4th February 2016) - Bulakhe, Ravindra N.; Sahoo, Sumanta; Nguyen, Thi Toan; Lokhande, Chandrakant D.; Roh, Changhyun; Lee, Yong Rok; Shim, Jae-Jin
Abstract : Schematic growth of copper sulfide as nanoflakes and nanotube like structure. Abstract : 3D copper sulfide (Cu2 S) with different morphologies for high performance supercapacitors were synthesized via a simple, cost effective successive ionic layer adsorption and reaction (SILAR) method. Further, these Cu2 S nanostructure demonstrate excellent surface properties like uniform surface morphology, large surface area of Cu2 S samples. X-ray diffraction (XRD) X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy of these samples confirmed the crystallinity and crystal structure of Cu2 S. The electrochemical studies of Cu2 S samples have been investigated by cyclic voltammetry, charge–discharge and electrochemical impedance spectroscopy techniques. The maximum specific capacitance of flower-like and integrated nanotubes samples are found 761 and 470 F g −1, respectively, at a scan rate of 5 mV s −1 . The electrodes are prepared using a simple four-beaker SILAR system at ambient conditions, thus providing an easy approach to fabricate high-power and high-energy supercapacitors. Further, EIS analysis shows a lower ESR value, high power performance, excellent rate as well as frequency response to flower-like Cu2 S sample. The Ragone plot shows better power and energy densities of all Cu2 S nanostructured samples. The long-term cycling performance of Cu2 S is examined with excellent retention of 95%. The high surface area provided by the porous and more conductive 3D nickel foam have been utilized properly to enhance the electrochemical properties of copper sulfides with charge transport and storage.